2017
DOI: 10.1590/s1677-5538.ibju.2016.0114
|View full text |Cite
|
Sign up to set email alerts
|

The change in serum Thiol/Disulphide homeostasis after transrectal ultrasound guided prostate biopsy

Abstract: Objectives The aim of this prospective clinical study was to investigate variations in a novel oxidative stress marker (thiol/disulphide homeostasis) in men who underwent transrectal ultrasound guided prostate biopsy (TRUSB).Materials and Methods A total of 22 men undergoing TRUSB of the prostate were enrolled in the study. Patients with abnormal digital rectal examination and/or total prostate specific antigen (PSA) over 4ng/mL underwent TRUSB with 12 cores. Serum samples were obtained before and just after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Similarly, authors have demonstrated that NT and TT levels decreased in patients underwent transrectal ultrasound guided prostate biopsy [107].…”
Section: Urological Disordersmentioning
confidence: 83%
“…Similarly, authors have demonstrated that NT and TT levels decreased in patients underwent transrectal ultrasound guided prostate biopsy [107].…”
Section: Urological Disordersmentioning
confidence: 83%
“…In addition, lower thiol levels might have a prognostic value in the development of chemotherapyinduced cardiac toxicity [15]. It has previously been observed that total thiol levels, native thiol levels and disulfide levels are decreased after a prostate biopsy [26], but it is unknown whether this has any prognostic significance. These results might lead to the assumption that patients should be treated with antioxidants to improve their prognosis.…”
Section: Conclusion and General Discussionmentioning
confidence: 99%
“…Some studies investigated oxidative markers in semen and urine (15). However, there are very few studies regarding thiol / disulphide in the field of urology (16, 17). In this paper, an invasive procedure such as a biopsy has been shown to increase oxidative stress in the prostate tissue (17).…”
Section: Discussionmentioning
confidence: 99%